Clinicopathological Profile of Colorectal Cancers in a Tertiary Care Hospital of Central, Nepal - Khatiwada, Sagar; Belbase, Narayan Prasad; Timilsina, Binay; Yadav, Prasun; Bhujel, Sushim; Shrestha, Nischal; Upadhyay, Hari Prasad (Journal of College of Medical Sciences-Nepal, 2023)
Introduction There is an increasing incidence of colorectal carcinoma (CRC) in developing countries like Nepal. The objective of this research is to study the CRC its demography, mode of presentation, type of surgery, complications and Histopathological evaluation (HPE) after surgery. Methods This was a retrospective descriptive observational study at College of Medical Sciences, Bharatpur, Nepal. Patients diagnosed with colorectal cancer admitted to gastrointestinal surgery department from July 2019 to June 2022 (3 years) were included. Data of patients were retrieved from hospital records. Pre-operative, intra-operative and post-operative diagnosis of CRC on HPE were also included in the study. Results Out of 52 CRC, males were 30 (57.7%) and females were 22 (42.3%), mean age was 52.7 years. Overall, left colon was affected in 33 (63.5%) and right in 19 (36.5%). More than one quarter of patients 14 (26.9%), had disease recurrence by 6 months follow-up. HPE revealed half of the disease condition as adenocarcinoma, moderately differentiated in (50%) cases. Conclusions Colorectal cancer is predominant in male patients and older age group. Incidence is high in younger people <40 years and low in extreme age group >80 years. Meticulous surgery is the only proven cure for malignancy.